Analisis Strategi Pelayanan untuk Meningkatkan Kualitas Layanan Berdasarkan Perspektif Ekonomi Islam - Maimunah, Maimunah; Rofiuddin, Mohammad (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2025)
Fierce competition in the healthcare industry requires service providers, including clinics, to prioritize service quality that is integrated with Islamic ethical values. Healthcare in Islam is viewed as the implementation of humanitarian values and worship, which must be based on the principles of Shiddiq, Amanah, Fathanah, and Tabligh (SAFT). This study aims to identify Dalwa Medical Clinic's service strategies and analyze their effectiveness in improving service quality based on the Islamic economic perspective. The study uses a qualitative approach with descriptive field research, where primary data is obtained through in-depth interviews with leaders, staff, and patients. The results show that the clinic's strategies, which focus on the quality of facilities, human resources, and patient relations, are in line with the principles of Shiddiq, Amanah, Fathanah, and Tabligh. However, significant obstacles were found in terms of operational efficiency, namely long waiting times at the pharmacy due to limited human resources. This gap indicates the need for managerial improvements to achieve the principle of Justice ('Adl) in service. The clinic's strategy is generally in line with Islamic ethics, but its effectiveness is not yet optimal, and improvements in human resource allocation and a more formal SOP structure are recommended.